ASI and Mini-ASI Thresher to separate rice grains from the panicle - CGIAR Research Program on Rice (2019)
The prototype has been fabricated, validated and standardize with private companies in Benin, Cameroon, Nigeria and Senegal. Technical drawings have been produced and publicly available.